Emergence of penicillin resistant Neisseria gonorrhoeae - Bhargava, D; Shakya, B; Mondal, KC; Rijal, BP (Journal of Institute of Medicine Nepal, 2010)
Introduction: Since the beginning of the modern chemotherapeutic era, the treatment of gonorrhea has been dogged by the shifting antimicrobial susceptibility of Neisseria gonorrhoeae. Though penicillins have been recommended for treatment of gonorrhoeae, there have been reports of treatment failure with penicillins. In this study, we report the emergence of penicillin resistance N. gonorrhoeae and its antimicrobial susceptibility pattern. Methods: Antibiotic sensitivity pattern of N. gonorrhoeae isolates from the male patients was determined by Kirby Bauer's Disc Diffusion method. The zone size was interpreted according to the Zone size interpretative chart. β-lactamase production was detected by Paper iodometric method. Results: A total of 30 isolates of N. gonorrhoeae were obtained from male patients with suspected acute gonococcal urethritis. Out of the 30 isolates, 18 (60.0%) were resistant to penicillin. Most of the penicillin resistant isolates were from the patients of age group 31 to 40 years (77.8%) followed by 21 to 30 years (53.3%) and 41 to 50 years (50.0%) (P>0.05). All isolates were sensitive to ceftriaxone. Similarly, 6 isolates were resistant to ciprofloxacin and 10 isolates were resistant to tetracycline. â- lactamase producer isolates were 16 in number. Conclusions: Penicillin resistant N. gonorrhoeae is on the rise in and around Birgunj. Thus, systematic surveillance of antibiotic sensitivity pattern of N. gonorrhoeae could be effective in detecting emergence of newly resistant strains before they become widespread in the community. DOI: http://dx.doi.org/10.3126/joim.v32i1.3996 Journal of Institute of Medicine, April, 2010; 32:1 pp.15-18